Association between incident cancer and subsequent stroke. Issue 2 (7th January 2015) - Navi, Babak B.; Reiner, Anne S.; Kamel, Hooman; Iadecola, Costantino; Elkind, Mitchell S. V.; Panageas, Katherine S.; DeAngelis, Lisa M.
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to examine the association between incident cancer and the subsequent risk of stroke. Methods Using the Surveillance, Epidemiology, and End Results–Medicare linked database, we identified patients with a new primary diagnosis of breast, colorectal, lung, pancreatic, or prostate cancer from 2001 through 2007. These patients were individually matched by age, sex, race, registry, and medical comorbidities to a group of Medicare enrollees without cancer, and each pair was followed through 2009. Validated diagnosis codes were used to identify a primary outcome of stroke. Cumulative incidence rates were calculated using competing risk survival statistics. Results Among 327, 389 pairs of cancer patients and matched controls, the 3‐month cumulative incidence of stroke was generally higher in patients with cancer. Cumulative incidence rates were 5.1% (95% confidence interval [CI] = 4.9–5.2%) in patients with lung cancer compared to 1.2% (95% CI = 1.2–1.3%) in controls (p < 0.001), 3.4% (95% CI = 3.1–3.6%) in patients with pancreatic cancer compared to 1.3% (95% CI = 1.1–1.5%) in controls (p < 0.001), 3.3% (95% CI = 3.2–3.4%) in patients with colorectal cancer compared to 1.3% (95% CI = 1.2–1.4%) in controls (p < 0.001), 1.5% (95% CI = 1.4–1.6%) in patients with breast cancer compared to 1.1% (95% CI = 1.0–1.2%) in controls (p < 0.001), and 1.2% (95% CI = 1.1–1.3%) in patients with prostate cancer compared to 1.1% (95% CI = 1.0–1.2%) in controls (p = 0.085). Excess risks attenuated over time and were generally no longer present beyond 1 year. Interpretation Incident cancer is associated with an increased short‐term risk of stroke. This risk appears highest with lung, pancreatic, and colorectal cancers. Ann Neurol 2015;77:291–300